2021
DOI: 10.1038/s41746-021-00393-9
|View full text |Cite
|
Sign up to set email alerts
|

Recalibration of deep learning models for abnormality detection in smartphone-captured chest radiograph

Abstract: Image-based teleconsultation using smartphones has become increasingly popular. In parallel, deep learning algorithms have been developed to detect radiological findings in chest X-rays (CXRs). However, the feasibility of using smartphones to automate this process has yet to be evaluated. This study developed a recalibration method to build deep learning models to detect radiological findings on CXR photographs. Two publicly available databases (MIMIC-CXR and CheXpert) were used to build the models, and four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Several previous study using the MIMIC-CXR database for modeling reported a DL model of CXR developed for accurately and automatically detecting pulmonary edema, atelectasis, consolidation, cardiomegaly, pneumothorax, and pleural effusion [43][44][45]. Compared with previously reported CXR scores or our CXR label models, the DL model of CXR has certain advantages and potential prospects for clinical application.…”
Section: Discussionmentioning
confidence: 94%
“…Several previous study using the MIMIC-CXR database for modeling reported a DL model of CXR developed for accurately and automatically detecting pulmonary edema, atelectasis, consolidation, cardiomegaly, pneumothorax, and pleural effusion [43][44][45]. Compared with previously reported CXR scores or our CXR label models, the DL model of CXR has certain advantages and potential prospects for clinical application.…”
Section: Discussionmentioning
confidence: 94%
“…There is no agreement on whether the richness and representativeness of public databases are sufficient to develop cardiomegaly detection algorithms with comparable performance on internal and external data sources. Three studies have demonstrated the external and internal validation resulting in similar AUC values from 0.800 to 0.828 38 , 52 , 53 , while Cohen et al 6 observed a drastic drop from 0.945 AUC to 0.721 AUC. Rajpurkar et al 32 observed that cardiomegaly is one of the lung abnormalities where automated detection results are significantly lower than the inter-observer variability.…”
Section: Discussionmentioning
confidence: 96%
“…The Madrid CXR images are resized during training to the input size for each of the pre-trained models (320 × 320 vs. 224 × 224) to output the imaging features for classification. The last fully connected layer of both models, containing 14 outputs corresponding to the 14 radiologic CheXpert finding labels [ 35 ], was removed. Instead, linearized convolutional features from either the second (− 2) or the fourth (− 4) to the last layer were used for the mortality prediction classification task.…”
Section: Methodsmentioning
confidence: 99%